LEVEL OF FINANCIAL LITERACY, TAXPAYER PERCEPTION, AND IMPLEMENTATION OF THE DIGITAL TAX SYSTEM “CORETAX” IN REDUCING TAX AVOIDANCE PRACTICES: (A CASE STUDY OF 100 MSMES IN BALI PROVINCE) - Muttiwijaya, Gede Teguh Prasetya; Rikky Rundu Padang; I Dewa Gede Anom Jambe Adnyana; I Made Pradana Adiputra; Rindhi Marverissa (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
CoreTax, launched by Indonesia’s Directorate General of Taxes in 2022 as part of the third reform phase, digitises tax services to improve efficiency, transparency, and integration. Its success depends not only on robust technology but also on taxpayers’ financial literacy and perceptions of the platform. Differences in these factors shape understanding, trust, and, ultimately, tax-avoidance behaviour. Survey data from 100 Bali-based MSMEs analysed with Partial Least Squares Structural Equation Modelling reveal that higher literacy and positive perceptions significantly boost CoreTax use, which in turn reduces tax avoidance, explaining 47 % of its variance. The results underline the need for fiscal-education initiatives and user-centred design enhancements so that CoreTax becomes a catalyst for sustained compliance among MSMEs.